THE EFFECT OF HUMAN DEVELOPMENT INDEX, COMPARISON RATIO GENDER AND INFLATION ON OPEN UNEMPLOYMENT RATE IN THE CITY OF MEDAN - Devi Andriyani; Dona Rivanka (Journal of Malikussaleh Public Economics, 2023)
This study examined the effect of the Human Development Index, Gender Ratio, and Inflation on the Open Unemployment Rate in Medan City. This study used secondary data obtained from the Central Bureau of Statistics during 2005-2020. The analytical method used was multiple linear regression analysis with the help of E-Views software. The results partially indicated that the Human Development Index (HDI) was negatively and significantly affected the Open Unemployment Rate in Medan City, the Gender Ratio positively and significantly affected the Open Unemployment Rate in Medan City, and Inflation negatively affected the Open Unemployment Rate in Medan City. Simultaneously, the Human Development Index, Gender Ratio, and Inflation positively and significantly influenced the open unemployment rate in Medan City.